RGEC: Menguak Kesehatan dan Potensi Financial Distress BTPN Syariah: RGEC: Uncovering the Health and Potential Financial Distress of BTPN Syariah - Cahyani, Renita; Lestari, Tina (Elektriese: Jurnal Sains dan Teknologi Elektro, 2025)
In the digital era and the transformation of the financial industry, Islamic banking plays a crucial role in strengthening the national financial system. Significant growth is reflected in the increase in assets of the Islamic banking industry in Indonesia, from IDR 441.79 trillion in 2021 to IDR 594.71 trillion in 2023 (OJK, 2024), indicating an increase in public trust in Sharia-based financial products. However, this growth is accompanied by challenges in the form of credit, market, and operational risks that can affect bank stability. This study focuses on PT Bank BTPN Syariah Tbk, which plays a crucial role in promoting financial inclusion for underprivileged communities. The objective of this study is to analyze the level of health and potential financial distress of Bank BTPN Syariah from 2021 to 2023 using the RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital) method, in accordance with POJK No. 4/POJK.03/2016. The research employs a descriptive approach, combining qualitative and quantitative methods, and utilizes secondary data from financial reports and literature studies. The results show that the NPF ratio remains healthy, despite an increase in 2022–2023. The FDR is in the Fairly Healthy category, and GCG has been ranked 2 (Healthy) for three consecutive years. ROA performed very well until 2022 but declined in 2023, while ROE tended to decline (Less Healthy). BOPO increased in 2023, indicating efficiency pressures, while CAR remained high and stable. Overall, PT Bank BTPN Syariah Tbk is a healthy and resilient institution, with recommendations for enhancing credit risk management and cost efficiency to maintain long-term stability.